Influence of Dietary Mixtures of Garlic and Ginger on Lipid Composition in Serum, Yolk, Performance of Pullet Growers and Laying Hens - Ademola , S.G.; Lawal, T.E.; Egbewande, O.O.; Farinu, G.O. (International Journal of Poultry Science, 2012)
Medicinal spices such as garlic and ginger contain chemical substances that could be used to enhance the value of food of animal origin. These substances such as organosulphur compounds of garlic and gingerone, shoagaols of ginger are responsible health benefits of these spices. The study investigated the addition of mixtures of garlic and ginger to diets of pullet chicks, growers and laying hens to evaluate beneficial effects on growth and egg production as well as their possible effects on lipid content of serum and yolk. Five diets were used for the study. Control diet was not supplemented with any of the mixtures. Four increasing levels of garlic (0.5%, 1.0%, 1.5% and 2.0%) were incorporated into diets for pullet chicks, growers and laying hens. Ginger supplements were also added to the diets at 0.5% and 0.75%. The results showed that the mixtures of garlic and ginger were beneficial by promoting final live weight of pullet growers, laying hens and also by lowering total cholesterol, triacylglycerol concentration in serum and yolk. Furthermore, the mixtures of garlic and ginger significantly (p<0.001) improved hen day production, egg weight and feed conversion. However, dietary inclusion of the mixtures significantly reduced shell weight and thickness. Significant (p<0.001) negative linear relationships were observed between dietary mixtures of garlic and ginger with parameters of serum and yolk lipids. In conclusion, the mixtures of garlic and ginger improved egg weight with lower cholesterol and triacylglycerol as well as better hen day production of laying hens. The results implied that the mixtures could benefit growth, laying performance and lowered yolk lipid content.